Highly Curated and Reliable E-Probes for Detection of Viral Pathogens in Unassembled High-Throughput Sequencing Datasets from Hops - Ali Pasha; Andres S. Espindola; Heiko Ziebell; Francisco M. Ochoa‐Corona (PhytoFrontiers)
Implementing high-throughput sequencing (HTS) in virus detection has recently become widespread. Bioinformatic expertise, programming skills, and access to high-capacity computers are essential for HTS data analysis. The E-Probe Diagnostic Nucleic Acid Analysis, a bioinformatic detection system that addresses these HTS constraints and performs searches on non-normalized HTS data, was adopted. The E-Probe Diagnostic Nucleic Acid Analysis theoretical framework was later updated for cross-platform accessibility via a web browser and renamed Microbe Finder (MiFi). In this study, the MiFi platform was used to design electronic probes (e-probes) for two viroids and three viruses that infect the hop plant (Humulus lupulus L.). These e-probes underwent a rigorous curation process followed by in silico validation to determine their theoretical limit of detection. Interestingly, curated 40-nt e-probes of all targeted pathogens in this study proved to have a better combination of sensitivity and specificity for their target genomes than other e-probe lengths. Additionally, an in vitro limit of detection analysis was performed by constructing an artificial positive control plasmid that contained all curated e-probes. The stock plasmid was serially diluted before sequencing to validate the detection limit. The curated and validated e-probes successfully detected the targeted pathogens when applied to HTS datasets previously analyzed using other bioinformatics tools. The e-probes developed in this study allow the direct detection of targeted hop viruses and viroids in unassembled HTS datasets. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.